Restrictions of the right of free movement on the territory of the country during the state of emergency, caused by the Sars-Cov-2 pandemic - Nikolova, Raina (Law Journal of New Bulgarian University, 2021)
The article analyzes the Bulgarian administrative legal framework on emergencies (state of emergency, crisis management and overcoming, emergency situation and emergency epidemic situation). It indicates the temporary restrictions of the right of free movement of the citizens provided in the legislation. The article discusses the competence of the central executive authorities, interdepartmental bodies and territorial authorities (regional governors and mayors) to deal with a pandemic. The article discusses also the legal basis and justifications for the introduction of the curfew by some of the regional governors and mayors during the state of emergency, caused by SARS-CoV-2 (COVID-19).